158 AN AUDIT ON DISCHARGE SUMMARIES IN A MEDICAL GERONTOLOGICAL WARD. (25th October 2022) - Makhura, RW; Nzeji, C; Rahaman, F; Fallon, A
Abstract: Background: Discharge summaries are an integral part of communication within healthcare to ensure safe care across settings. Alterations are documented and relayed between relevant healthcare professionals. This audit evaluates quality of discharge summaries from a medical gerontology ward against the National Standard for Patient Discharge Summary Information (HIQA) Methods: A retrospective audit was carried out with data collected from a ward discharge registry over 3-months (February-April 2022) and associated discharge summaries. Results: A total of 31 discharges (including death) were identified during the set period, 97% (n=30) of which had completed discharge summaries. Upon assessment against the standard, 100% (n=30) included details vital to patient identification including name, date of birth, gender and address. In addition, 100% (n=30) included information on date of admission-discharge, clinical course, relevant investigations, treatments, procedures, discharge medications and details of the doctor completing the discharge summary. The audit identified that 20% (n=6) of summaries stated referral source, which is mandatory according to the standard. 13% (n=4) included dietary interventions and 0% included immunization information (whether as an inpatient or prior). Regarding information on further management, 77% (n=23) had guidance on follow-up hospital care, 27% (n=8) had information about social care actions, 20% had advice, recommendations and future plans documented and in 10% information was documented to be given to patient and carer. Conclusion: Compliance with mandatory information including patient details, admission/discharge date, diagnoses, hospital course, and author fully met the standard. However, there was poor compliance with information relevant to continuation of patient care in the community. This is particularly relevant for older patients with multiple co-morbidities and complex care needs. Doctors working on this ward are receiving education regarding the importance of documentation of functional status, social care needs and diet at discharge. In future, mandatory documentation as part of electronic discharge summaries may improve compliance and continuity of care across settings.